2019
DOI: 10.1088/1748-0221/14/01/p01025
|View full text |Cite
|
Sign up to set email alerts
|

A newly developed prototype magnetic sector mass spectrometer with high resolving power

Abstract: In recent years, high-resolution mass spectrometers have been applied and made tunable to various fields. In this study, a prototype magnetic sector mass spectrometer with high resolving power has been developed. Its design is based on employing a 90 • magnetic sector-field analyzer with double trajectory, a miniature Nier-type ion source and two channel-type electron multipliers for ion detection. The ion accelerating voltage is controllable from 200 to 2500 V and the mass range demonstrated herein is (1-73) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Yan et al. [32] reported that increasing the exit slit to 1.5 mm further improved the ionization efficiency.…”
Section: Instrumentation Of Portable Mass Spectrometersmentioning
confidence: 99%
See 2 more Smart Citations
“…Yan et al. [32] reported that increasing the exit slit to 1.5 mm further improved the ionization efficiency.…”
Section: Instrumentation Of Portable Mass Spectrometersmentioning
confidence: 99%
“…Li et al [30] designed a miniature EI source which employs two identical rhenium-tungsten filaments featuring longer lifetime and improved stability with a power consumption of 15 W. Meng et al [31] developed the ionization chamber with a dimension of 12 × 12 × 7 mm 3 and an exit slit that is 1 mm wide. Yan et al [32] reported that increasing the exit slit to 1.5 mm further improved the ionization efficiency.…”
Section: Electron Ionizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common instrumentation used for such measurements are sector instruments. Sector instruments provide very stable ion beams and separate ions spatially, allowing for a multicollector detection system . Multicollector detector arrays traditionally consist of either faraday cup detectors (FC), electron multipliers (EM), or a combination of both depending on the application.…”
Section: Introductionmentioning
confidence: 99%
“…Sector instruments provide very stable ion beams and separate ions spatially, allowing for a multicollector detection system. 18 Multicollector detector arrays traditionally consist of either faraday cup detectors (FC), 19 electron multipliers (EM), 20 or a combination of both depending on the application. Generally, faraday cups will have a longer lifetime and provide a linear response with the ion signal and are useful for measuring high abundance ions.…”
Section: ■ Introductionmentioning
confidence: 99%